The broken broker system? Transacting on agricultural wholesale markets in India (Uttarakhand) - Minten, Bart; Vandeplas, Anneleen; Swinnen, Johan (International Food Policy Research Institute, 2011)
There is a vigorous debate on liberalization of the heavily regulated agricultural markets in India. A crucial institutional characteristic is the role of state-regulated brokers in wholesale markets. Relying on data from a unique survey in Uttarakhand, a state in North India, we find that regulations on margins are ineffective, since most brokers charge rates that significantly exceed the regulated ones. We also find that a majority of farmers self-select into long-term relationships with brokers. These relationships allow some of the farmers to interlink credit and insurance markets to the agricultural output market. This interlinkage does not, however, appear to be an instrument for farmer exploitation (since it does not lead to worse inputs, higher interest rates, or lower implicit output prices) but is seemingly an extra service provided by brokers to establish farmer loyalty and thereby ensure future supplies.